Regionalization of wheat powdery mildew oversummering in China based on digital elevation - Ya-fei ZOU; Hong-bo QIAO; Xue-ren CAO; Wei LIU; Jie-ru FAN; Yu-li SONG; Bao-tong WANG; Yi-lin ZHOU (Journal of Integrative Agriculture)
Blumeria graminis f. sp. tritici, the pathogen that causes wheat powdery mildew, is one of the most important diseases affecting wheat production in China, and the oversummering is the key stage of wheat powdery mildew epidemic. The more oversummering regionalization of wheat powdery mildew has played an important role in disease prediction, prevention and control. In this study, we analyzed the correlation between oversummering data of wheat powdery mildew and the meteorological factors over the past years, and determined that temperature was the key meteorological factor influencing oversummering of wheat powdery mildew. The average temperature at which wheat powdery mildew growth was terminated (26.2°C) was used as the threshold temperature to regionalize the oversummering range of wheat powdery mildew. This regionalization was done using the GIS ordinary kriging method combined with the Digital Elevation model (DEM) of China. The results showed that annual probability of oversummering region based on Model 26.2 were consistent with the actual survey of the more summer wheat powdery mildew. Wheat powdery mildew oversummering regions in China mainly cover mountainous or high-altitude areas, and these regions form a narrow north-south oversummering zone. Oversummering regions of wheat powdery mildew is mainly concentrated in the high-altitude wheat growing areas, including northern and southern Yunnan, northwestern Guizhou, northern and southern Sichuan, northern and southern Chongqing, eastern and southern Gansu, southeastern Ningxia, northern and southern Shaanxi, central Shanxi, western Hubei, western Henan, northern and western Hebei, western Liaoning, eastern Tibet, eastern Qinghai, western Xinjiang and other regions of China.